2010
DOI: 10.1021/am100696v
|View full text |Cite
|
Sign up to set email alerts
|

Organic Field-Effect Transistor/Memory Devices with Pentacene/Polydiacetylene Composite Film As Active Channel Material: A Morphology Dependence Study

Abstract: Composite films of pentacene and poly(10,12-pentacosadiynoic acid) were prepared and used as the active channel material in a top-contact, bottom-gate field-effect transistor. The transistors exhibited high field-effect mobility as well as large I-V hysteresis as a function of gate bias history. The polydiacetylenic moieties incorporated in the pentacene film served as charge storage vehicles, which affected the threshold voltage shifts and created the electric bistability needed in a memory device. The memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…These thicknesses are similart ob ut smaller than twice the molecular thickness and are systematicallyt hinner than those with odd chains. It wass hown previously [25] by attenuated total reflectance (ATR) IR that these films gave an IR absorption at 1685 cm À1 ,t he same as the carbonyl stretching frequency for hydrogen-bond dimers of carboxylic acid in their solids tate. This suggestst he formation of the dimer layer.Aplot of the thickness versus the chain length ( Figure S1 in the Supporting Information) shows that the odd chain and even chain systems fall on two linear curves with different slopes.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These thicknesses are similart ob ut smaller than twice the molecular thickness and are systematicallyt hinner than those with odd chains. It wass hown previously [25] by attenuated total reflectance (ATR) IR that these films gave an IR absorption at 1685 cm À1 ,t he same as the carbonyl stretching frequency for hydrogen-bond dimers of carboxylic acid in their solids tate. This suggestst he formation of the dimer layer.Aplot of the thickness versus the chain length ( Figure S1 in the Supporting Information) shows that the odd chain and even chain systems fall on two linear curves with different slopes.…”
Section: Resultsmentioning
confidence: 90%
“…[23,24] Recently, in an effort to use polymerized films of this compound for charge storage purposesi n memory device fabrication, we observed au nique ring formation on silica surfaces upon vacuum deposition of PDA. [25] This raisest he possibility of pre-organizing the molecules into specific patterns for conjugated polymer formation. In this work, we investigated as eries of long-chain carboxylic acids containing diacetylene units at different positions along the chain (i.e., C 12 H 25 (CC) 2 (CH 2 ) n COOH, n = 7-11) and demonstrated that unique film morphologies (dendrite-o rr ing-type forms) were observed depending on whether the spacer length between the diacetylene unit and the carboxylh ead group is an odd carbon number or even carbon number (odd-even effect).…”
Section: Introductionmentioning
confidence: 99%
“…The trapped charge within the film could be supplied by a gate electrode, as in the case of an organic transistor ( Figure 8A), of the same type as others found in literature using other materials (e.g., pentacene) [31][32][33], or by a biochemical redox reaction, catalyzed by a bio-recognition element, such as an enzyme, and involving a substrate, a target analyte, and a product in an enzyme field effect transistor (ENFET) biosensor based on these organic transistors ( Figure 8B). The use of the films studied in this work would have all the properties of biocompatibility and non-toxicity desired for biosensors.…”
Section: Characterization Of Organic Memoriesmentioning
confidence: 77%
“…[2] Beyond the intrinsic molecular properties, it has been demonstrated that the intermolecular interactions between the optoelectronic materials in organic light-emitting diodes (OLEDs), organic photovoltaics (OPVs), and organic fieldeffect transistors (OFETs) often play decisive roles in determining the ultimate performance of the assembled devices. [3] In this regard, organogels provide an excellent model for evaluating the intermolecular interactions and subsequent applications in optoelectronic devices. [4] Recently, there has been growing interest in the study of metallogels, owing to the rich spectroscopic and luminescence properties exhibited by a variety of transition-metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes Pt-bp1 and Pt-bp3 displayed a structureless band at l = 508 and 498 nm, respectively, with emission lifetimes of hundreds of nanoseconds. The emission of both Pt-bp1 and Pt-bp3 are tentatively assigned to dp(Pt)-p*A C H T U N G T R E N N U N G (bpy) 3 MLCT transitions. [5a, 7] Structured emissions were observed for Pt-ep1 and Pt-ep3, and are assigned to a Pt-perturbed PEt 3 localized triplet emission.…”
Section: Introductionmentioning
confidence: 99%